1981
DOI: 10.1007/bf00709624
|View full text |Cite
|
Sign up to set email alerts
|

Homicidal school-age children: Cognitive style and demographic features

Abstract: This paper reviews the literature regarding homicide in children and discusses the various hypotheses regarding the etiology of murderous aggression. The relationship of perceived locus of control as a cognitive style and homicidal behavior in children is discussed. A comparison of children matched for severity of illness, sex, age, and intelligence is described which found the nine homicidal children, ages 6 to 11, to perceive themselves as more externally controlled than the comparison group of children hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Review of the clinical literature revealed only a few instances in which the child murderers were psychotic or otherwise seriously mentally ill (see Ewing, 1990). Petti and Davidman (1981), for example, conducted a study on nine children (ages 6-11) hospitalized for homicidal aggression. Although none of these children were diagnosed as psychotic, three were characterized as borderline psychotic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Review of the clinical literature revealed only a few instances in which the child murderers were psychotic or otherwise seriously mentally ill (see Ewing, 1990). Petti and Davidman (1981), for example, conducted a study on nine children (ages 6-11) hospitalized for homicidal aggression. Although none of these children were diagnosed as psychotic, three were characterized as borderline psychotic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research specifically investigating "little kids" who kill has also been sparse, partly because of its low incidence and the difficulty of obtaining access to these youth (see, e.g., Bender, 1959;Carek & Watson, 1964;Ewing, 1990;Goetting, 1989Goetting, , 1995Petti & Davidman, 1981;Pfeffer, 1980;Shumaker & Prinz, 2000;Tooley, 1975). The importance of distinguishing between preadolescents and adolescents in understanding what motivates youth to kill and in designing effective treatment plans was recognized by clinicians as early as 1940 (Bender & Curran, 1940).…”
Section: Homicides Involving Young Children As Offendersmentioning
confidence: 99%
“…Individuals who are diagnosed as psychotic have lost touch with reality, often experience hallucinations (seeing or hearing things that are not occurring) and delusions (bizarre beliefs), and behave inappropriately. Most studies report that JHOs are rarely psychotic (see, e.g., Bailey, 1994;Corder, Ball, Haizlip, Rollins, & Beaumont, 1976;Cornell, 1989;Cornell et al, 1987bCornell et al, , 1989Dolan & Smith, 2001;Ewing, 1990;Hellsten & Katila, 1965;Kashani, Darby, Allan, Hantke, & Reid, 1997;King, 1975;Labelle et al, 1991;Malmquist, 1971;Myers et al, 1995;Myers & Kemph, 1988Patterson, 1943;Petti & Davidman, 1981;Russell, 1965Russell, , 1979Shumaker & McKee, 2001;Sorrells, 1977;Stearns, 1957;Walshe-Brennan, 1974Yates, Beutler, & Crago, 1983; with respect to adolescent mass murderers, see Meloy, Hempel, Mohandie, Shiva, & Gray, 2001). Some studies, however, do posit a high incidence of psychosis (see, e.g., Bender 1959;Lewis, Pincus et al, 1988;Rosner, Weiderlight, Rosner, & Wieczorek, 1978;Sendi & Blomgren, 1975) or episodic psychotic symptomatology (Lewis et al, 1985;Lewis, Lovely et al, 1988;Myers et al, 1995;Myers & Scott, 1998) and other serious mental illness, such as mood disorders (Lewis, Pincus et al, 1988;Malmquist, 1971Malmquist, , 1990.…”
Section: Psychological Disorder and Youth Homicidementioning
confidence: 99%
See 2 more Smart Citations